Fast Food Industry: Brand Association and Perceived Quality Influence on Purchase Intention of Millennial Consumers - Clarissa Reyes Magbanua; Trixine Marie Gatdula Olfato; Anne Cheri Marie Nocon Redota; Antonio Jr. Etrata (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2023)
Fast food restaurants often attract their target consumers with their taste, price, and level of customer service. Specific dimensions must also be considered when making purchases to attract customers to these restaurants. This study aims to give new entrants in the fast food business a basis for what they should concentrate on to draw in Generation Y customers. 385 participants received an online survey, and descriptive statistics, PLS-SEM, WARP PLS Version 7.0, and SPSS Version 20 were utilized to examine the quantitative data. Results showed that respondents regarded service quality as the most significant factor, meaning it is more important that employees treat them well in a fast food restaurant for them to return from the same restaurant. On the other hand, brand association is not as crucial as the other factors. Nonetheless, it still influences the purchase intention in the industry through the awareness it provides regarding updates on the new entrants to fast food in the Philippines.